2022
DOI: 10.1080/08897077.2021.1931633
|View full text |Cite
|
Sign up to set email alerts
|

Project ECHO and Primary Care Buprenorphine Treatment for Opioid use Disorder: Implementation and Clinical Outcomes

Abstract: Background: Our rural health system sought to (1) increase the number of primary care clinicians waivered to prescribe buprenorphine for treatment of opioid use disorder (OUD) and (2) consequently increase the number of our patients receiving this treatment. Methods: We used the Project for Extension for Community Health Outcomes (ECHO) tele-education model as an implementation strategy. We examined the number of clinicians newly waivered, the number of patients treated with buprenorphine, the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…One study from a program designed to support treatment of opioid use disorder found a moderate correlation between number of buprenorphine prescriptions and number of sessions attended, an observation aligned with our findings. 39 Our analysis also identified a positive indirect effect of Project ECHO on VL suppression, with statistically significant improvements for patients of lower-volume providers who do not participate in Project ECHO themselves but work in the same clinic system as a provider who does participate. This is an intentional goal of Project ECHO: to promote care champions who will share knowledge and resources with local colleagues.…”
Section: Discussionmentioning
confidence: 58%
“…One study from a program designed to support treatment of opioid use disorder found a moderate correlation between number of buprenorphine prescriptions and number of sessions attended, an observation aligned with our findings. 39 Our analysis also identified a positive indirect effect of Project ECHO on VL suppression, with statistically significant improvements for patients of lower-volume providers who do not participate in Project ECHO themselves but work in the same clinic system as a provider who does participate. This is an intentional goal of Project ECHO: to promote care champions who will share knowledge and resources with local colleagues.…”
Section: Discussionmentioning
confidence: 58%
“…[33][34][35] Support for buprenorphine prescribers like that provided by New Jersey's 2 MAT COEs, can also increase buprenorphine prescribing. [35][36][37] Importantly, synergistic factors unique to New Jersey may account for the changes in buprenorphine use and prescribing observed in this study.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, in primary care, where providers rely on referral networks and specialists for co-management of complex conditions, access to addiction medicine specialists and behavioral health providers is crucial. Interventions that connect PCPs with specialists, provide continuing education, and increase access to behavioral health providers have been shown to increase the number of waivered PCPs and MOUD access in primary care 31–35 . To address the lack of clinical capacity endorsed by some PCPs, interventions that expand telemedicine prescribing and establish MOUD comanagement with nurse care managers and pharmacists also have been successful 36–38 .…”
Section: Discussionmentioning
confidence: 99%
“…Interventions that connect PCPs with specialists, provide continuing education, and increase access to behavioral health providers have been shown to increase the number of waivered PCPs and MOUD access in primary care. [31][32][33][34][35] To address the lack of clinical capacity endorsed by some PCPs, interventions that expand telemedicine prescribing and establish MOUD comanagement with nurse care managers and pharmacists also have been successful. [36][37][38] Stigma, although a well-documented barrier to buprenorphine treatment in primary care in the past, 17 did not emerge as a prominent barrier in our study.…”
Section: Discussionmentioning
confidence: 99%